Mercy Watson thinks like a pig - DiCamillo, Kate (DiCamillo, Kate. Mercy Watson collection ;, 2008)
After Mercy Watson follows the delightful scent and delicious taste of the pansies her thoughtful neighbors plant to beautify their yard, Animal Control Officer Francine Poulet is called out to handle the case, which brings unexpected results.